Handbook of communication and emotion research, theory, applications, and contexts - Andersen, Peter A.; Guerrero, Laura K. (San Diego : Academic Press, 1998)
Emotion is once again at the forefront of research in social psychology and personality. The Handbook of Communication and Emotion provides a comprehensive look at the questions and answers of interest in the field: How are specific emotions (fear, jealousy, anger, love) communicated? How does the effectiveness, or ineffectiveness, of this communication affect relationships? How is the communication of emotion utilized to deceive, or persuade, others? This important reference work is edited by top researchers in the field of communication and authored by a who's who in emotion and communication. Key Features * Provides a comprehensive look at the role of communication in emotion * Includes contributions from top researchers in the field of communications * Examines how specific emotions are communicated * Includes important new research on the effect of communication on relationships.
Communication and emotion : basic concepts and approaches / Laura K. Guerrero, Peter A. Andersen, and Melanie R. Trost -- Communicating emotion in everyday life : cues, channels, and processes / Sally Planalp -- Principles of communication and emotion in social interaction / Peter A. Andersen and Laura K. Guerrero -- Strategic embarrassment : the culprit of emotion / Lisa Bradford and Sandra Petronio -- Guilt and hurt : similarities, distinctions, and conversational strategies / Anita L. Vangelisti and Rhonda J. Sprague -- Jealousy experience and expression in romantic relationships / Laura K. Guerrero and Peter A. Andersen -- The experience and expression of anger in interpersonal settings / Daniel J. Canary, Brian H. Spitzberg, and Beth A. Semic -- Interpersonal communication problems associated with depression and loneliness / Chris Segrin -- How the comforting process works : alleviating emotional distress through conversationally induced reappraisals / Brant R. Burleson and Daena J. Goldsmith -- When a friend is in need : feelings about seeking, giving, and receiving social support / Anita P. Barbee, Tammy L. Rowatt, and Michael R. Cunningham -- The bright side of relational communication : interpersonal warmth as a social emotion / Peter A. Andersen and Laura K. Guerrero -- Loving and liking / Carolyn B. Taraban, Susan S. Hendrick, and Clyde Hendrick -- Communication and sexual desire / Sandra Metts, Susan Sprecher, and Pamela C. Regan -- Emotional expression in the deception process / David B. Buller and Judee K. Burgoon -- Affect, persuasion, and communication processes / Peter F. Jorgensen -- Fear as motivator, fear as inhibitor : using the extended parallel process model to explain fear appeal successes and failures / Kim Witte -- Cultural influences on emotional expression : implications for intercultural communication / Richard E. Porter and Larry A. Samovar -- Emotion, attachment, and satisfaction in close relationships / Judith A. Feeney, Patricia Noller, and Nigel Roberts -- Communication of emotions in friendships / Stanley O. Gaines, Jr., [et al.] -- Children's responses to emotional potrayals on television / Barbara J. Wilson and Stacy L. Smith.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Interpersonal communication; Expression; Emotions; Communication; Expressed Emotion; Electronic books